Islam Hadhari dalam Konteks Ketamadunan, Budaya dan Agama di Malaysia - Mohd Hambali, Khadijah (Jurnal Usuluddin, 2004)
Islam Hadhari or Civilisational Islam has been spelt out in the context of the Malay community s struggle for independence and development, with an emphasis on enhancing the quality of life. This would be achieved through the acquisition of knowledge, the development of the individual and the nation and the establishment of a dynamic economic, trading and financial system. Such a balanced development would produce an ummah or community of knowledgeable and pious people with noble values like honesty and trustworthiness, and who would be able to take on global challenges. It could well be a paradigm of how Malaysians Muslims should see Islam in the context of a multi-racial Malaysia facing a changing world. Considering the sensitivity of the non-Muslim community towards the increasing Islamisation of Malaysia, this article tries to undertake an analysis the concept of Islam Hadhari as well as masyarakat Madani by emphasizing the vision for Malaysians Muslims to focus more on Islamic values as well as personal and economic development. Malaysians Muslims should use the glorious of Islamic civilization in all aspects to inspire them to achieve prosperity.